2015
DOI: 10.22201/ib.20078706e.2012.4.1267
|View full text |Cite
|
Sign up to set email alerts
|

Regionalización y relaciones biogeográficas de la Península de Yucatán con base en los patrones de distribución de la familia Leguminosae

Abstract: Resumen. Se analizaron los patrones de distribución geográfica de 224 especies de leguminosas nativas de la Península de Yucatán (México) en 48 unidades geográficas operativas (0.5° de latitud y 0.5 ° longitud). Las relaciones biogeográficas regionales se determinaron utilizando información de las leguminosas de 12 áreas de América Central, América del Norte, América del Sur y las Antillas. Se emplearon 3 métodos de análisis: coeficiente de Jaccard, análisis de parsimonia (PAE) y un análisis de patrones genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
1
4
0
4
Order By: Relevance
“…This agrees with results of secondary vegetation studies carried out in the Yucatan Peninsula [58][59][60][61][62][63]. Other authors like and Sánchez & Islebe [64] and De Stefano et al [65] found that the Fabaceae family is particularly diverse in the southern region of the Yucatan Peninsula due to the precipitation gradient and its biogeographical affinity to the biota of Central America. Furthermore, it has been widely reported that it is the dominant family in secondary vegetation at different successional stages [66][67][68][69].…”
Section: Composition and Floristic Richnesssupporting
confidence: 89%
“…This agrees with results of secondary vegetation studies carried out in the Yucatan Peninsula [58][59][60][61][62][63]. Other authors like and Sánchez & Islebe [64] and De Stefano et al [65] found that the Fabaceae family is particularly diverse in the southern region of the Yucatan Peninsula due to the precipitation gradient and its biogeographical affinity to the biota of Central America. Furthermore, it has been widely reported that it is the dominant family in secondary vegetation at different successional stages [66][67][68][69].…”
Section: Composition and Floristic Richnesssupporting
confidence: 89%
“…La región Neotropical comprende las provincias de las Tierras Bajas del Pacífico, Cuenca del Balsas y Veracruzana. Contribuciones posteriores han reconocido distritos dentro de algunas de estas provincias (Escalante et al, 2007;Torres-Miranda y Luna, 2007;Espinosa-Organista et al, 2008;Ramírez-Barahona et al, 2009;Duno-de Stefano et al, 2012;Gámez et al, 2012;Morrone, 2014aMorrone, , 2017a. Morrone et al (2017) proporcionaron un mapa actualizado de las provincias biogeográficas mexicanas ( fig.…”
Section: Regionalización Biogeográfica De Méxicounclassified
“…Regionalización biogeográfica. La regionalización biogeográfica de esta provincia ha tenido una historia compleja, con distintas unidades reconocidas de acuerdo con los taxones analizados (Arriaga et al, 1997;Barrera, 1962;Duno-de Stefano et al, 2012;Espadas-Manrique et al, 2003;Ibarra-Manríquez et al, 2002). Dentro de esta provincia se han reconocido 4 distritos (Morrone, 2017a): Norte de Yucatán, Rooeño, Petén y Bosques Pantanosos Beliceños.…”
Section: Provincia De La Península De Yucatánunclassified
“…Some authors have highlighted the strong floristic affinity of the YPBP with Central America and Mexico (Miranda, 1958; Estrada-Loera, 1991; Ibarra-Manríquez et al, 2002; Duno de Stefano et al, 2012). However, this region has significantly different environmental restrictions compared to contiguous geographic areas, including complex microtopology and northwest-to-southeast edaphic and climate gradients (Vargas et al, 2014).…”
Section: Discussionmentioning
confidence: 99%